Improving clean water access for fishermen communities in Khaidir village environment 6 Nelayan Indah sub-district Medan Labuhan district Medan city - Dharma, Surya; Marsaulina, Irnawati (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
The Community Service Program (PPM) aims to improve the knowledge and skills of coastal communities through water filter science and technology by using media consisting of quartz sand, 1-3 cm diameter gravel, activated charcoal and alum. Long-term goals can improve the quality of life and avoid people from waterborne diseases so that the degree of public health improves. This community service was carried out in Kampung Khaidir Lingkungan 6 Kelurahan Nelayana Indah, Medan Labuhan District, Medan City. In order to achieve these objectives several stages of activities are carried out. First is the initial survey activity to find out the location for the drilling of the well that will be used by the local community. The second stage is to build a Bor well unit. The third stage socializes the use of Bor wells access to clean water and changes people's behavior so they behave in a clean and healthy life. This community service program is carried out within 6 months. The targets and outcomes of this program are: (1). Access to Bor wells Clean Water. The community masters the science and technology of making Bor wells to be a source of water that meets health requirements as well as meeting the need for clean water for 22 Fishermen Families in Kampung khaidir Neighborhood 6 Kelurahan Indah Fishermen District Medan Labuha District. (2). The Clean and Healthy Life Behavior of the community increases based on the posttest and observation of the living environment. (3). The decreasing prevalence of diseases transmitted through water media such as diarrhea, skin diseases so that the degree of public health increases and community productivity also increases.